Perancangan Sistem Informasi Pelayanan Pelanggan Kelompok Masyarakat Berpenghasilan Rendah (MBR) Berbasis Web - setiawansyah13 setiawansyah13 (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2021)
The Way Rilau Water Company (PDAM) is a regional government company in the city of Bandar Lampung which is engaged in drinking water management. The data collection process for assistance starts with the collection of files collected at the RT head in the form of KTP, KK, NPWP, proof of tax payment, the last electricity bill. After that the community filled out the registration form provided by the RT. Then the registration form file is given to the village head to be deposited with the company, until finally obtaining a permit for pipe installation from the PDAM company is done manually. Many of the files that have been collected are tucked away so that the community will find it difficult to obtain an installation permit. The customer service information system for low-income community groups used, namely usecase diagrams, CRC cards, class diagrams, and implementation of customer service systems for low-income community groups were made using the CodeIgniter framework and using the MySQL database. Results The design of a customer service system for low-income community groups is designed using the extreme programming development method which is also faster in the research process because it can produce applications with a performance efficiency level of 81%. The results of testing the functionality of the system using blackbox testing were 100%, and the results of web quality 4.0 testing were 86%